Given :
y= -8x-6
y= -3x +4
By solving it, we get,
-8x-6 = -3x+4
![= > x = - 2](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20x%20%3D%20%20-%202)
Substituting the value of "x" in second given equation,
![y = - 3x + 4](https://tex.z-dn.net/?f=y%20%3D%20%20-%203x%20%2B%204)
![= > y = - 3 \times ( - 2) + 4](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20y%20%3D%20%20-%203%20%5Ctimes%20%28%20-%202%29%20%2B%204)
By solving it, we get,
![y = 10](https://tex.z-dn.net/?f=y%20%3D%2010)
Hence, the values are :-
![x = - 2 \\ y = 10](https://tex.z-dn.net/?f=x%20%3D%20%20-%202%20%5C%5C%20y%20%3D%2010)
Awnser is 8<span>6<span>√m</span></span>+3<span>n2</span><span>8<span>√<span>m<span>5 add me as brainliest pls</span></span></span></span>
Answer:
9.8
Step-by-step explanation:
Answer:
A-B really simple.
Step-by-step explanation:
Answer:
226.981
Step-by-step explanation:
The volume of a cube is found using the formula V = s³. Substitute s = 6.1 and simplify.
V = s³
V = (6.1)³
V = (6.1)(6.1)(6.1)
V = 226.981